Effect of mountain ultra-marathon running on plasma angiopoietin-like protein 4 and lipid profile in healthy trained men - Górecka, Monika (Eur J Appl Physiol, 2019)
PURPOSE: Angiopoietin-like protein 4 (ANGPTL4) regulates lipid metabolism by inhibiting lipoprotein lipase activity and stimulating lipolysis in adipose tissue. The aim of this study was to find out whether the mountain ultra-marathon running influences plasma ANGPTL4 and whether it is related to plasma lipid changes. METHODS: Ten healthy men (age 31 ± 1.1 years) completed a 100-km ultra-marathon running. Plasma ANGPTL4, free fatty acids (FFA), triacylglycerols (TG), glycerol (Gly), total cholesterol (TC), low (LDL-C) and high (HDL-C) density lipoprotein-cholesterol were determined before, immediately after the run and after 90 min of recovery. RESULTS: Plasma ANGPTL4 increased during exercise from 68.0 ± 16.5 to 101.2 ± 18.1 ng/ml (p < 0.001). This was accompanied by significant increases in plasma FFA, Gly, HDL-C and decreases in plasma TG concentrations (p < 0.01). After 90 min of recovery, plasma ANGPTL4 and TG did not differ significantly from the exercise values, while plasma FFA, Gly, TC and HDL-C were significantly lower than immediately after the run. TC/HDL-C and TG/HDL-C molar ratios were significantly reduced. The exercise-induced changes in plasma ANGPTL4 correlated positively with those of FFA (r = 0.73; p < 0.02), and HDL-C (r = 0.69; p < 0.05). Positive correlation was found also between plasma ANGPTL4 and FFA concentrations after 90 min of recovery (r = 0.77; p < 0.01). CONCLUSIONS: The present data suggest that increase in plasma FFA during mountain ultra-marathon run may be involved in plasma ANGPTL4 release and that increase in ANGPTL4 secretion may be a compensatory mechanism against fatty acid-induced oxidative stress. Increase in plasma HDL-C observed immediately after the run may be due to the protective effect of ANGPTL4 on HDL.